Management of borderline ovarian tumours during pregnancy: Results of a French multi-centre study. (January 2021) - Zilliox, M.; Lecointre, L.; Azais, H.; Ballester, M.; Bendifallah, S.; Bolze, P.A.; Bourdel, N.; Bricou, A.; Canlorbe, G.; Carcopino, X.; Chauvet, P.; Collinet, P.; et al.
Abstract: Objective: To assess the diagnostic and prognostic characteristics of borderline ovarian tumours (BOTs) detected during pregnancy, and to establish an inventory of French practices. Materials and methods: A retrospective multi-centre case study of 14 patients treated for BOTs, diagnosed during pregnancy between 2005 and 2017, in five French pelvic cancerology expert centres, including data on clinical characteristics, histological tumour characteristics, surgical procedure, adjuvant treatments, follow-up and fertility. Results: The mean age of patients was 29.3 [standard deviation (SD) 6.2] years. Most BOTs were diagnosed on ultrasonography in the first trimester (85.7 %), and most of these cases (78.5 %) also underwent magnetic resonance imaging to confirm the diagnosis (true positives 54.5 %). Most patients underwent surgery during pregnancy (57 %), with complete staging surgery in two cases (14.3 %). Laparoscopy was performed more frequently than other procedures (50 %), and unilateral adnexectomy was more common than cystectomy (57.5 %). Tumour size influenced the surgical approach significantly (mean size 7.5 cm for laparoscopy, 11.9 cm for laparoconversion, 14 cm for primary laparotomy; P = 0.08), but the type of resection did not. Most patients were initially diagnosed with International Federation of Gynecology and Obstetrics stage IA (92.8 %) tumours, but many were upstaged after complete restaging surgery (57.1 %). Most BOTs were serous (50 %), two cases had a micropapillary component (28.5 %), and one case had a micro-invasive implant. BOTs were bilateral in two cases (14.2 %). Mean follow-up was 31.4 (SD 14.8) months. Recurrent lesions occurred in two patients (14.2 %) and no deaths have been recorded to date among the study population. Conclusion: BOTs remain rare, but this study – despite its small sample size – supports the hypothesis that BOTs during pregnancy have potentially aggressive characteristics.